Nonclassical properties of light in atom-cavity interaction scheme with time-and intensity-dependent coupling / Nor Hazmin Sabri - Sabri, Nor Hazmin (2013)
The nonclassical properties of light and atomic dynamics are studied. The system considered are two level atom interact with a quantized field in a high quality cavity, which is recognized as the Jaynes-Cumming Model. The time- and intensity-dependent atom-field coupling are applied to the system, with different initial field states and initial atomic states. We also extend the system for three level atom in a cavity, and include the dissipative mechanism in the system. We consider the laser driven three level atom in a cavity coupled to a reservoir. Interesting effects of the transient coupling are analyzed through the collapse-revival pattern in population inversion, while the nonclassicality of cavity field is studied through the features in the evolution ofWigner function. The inversion of initial superposed atomic state seems to be independent of initial classical fields but can be stimulated by the Schrodinger cat field. In two level system, the oscillatory coupling coefficient can prolong the occurrence of collapse, in analogy to the Zeno effect.The intensity atom-field coupling duration is an important parameter for controlling atomic inversion and producing frozen nonclassical light in the cavity after the atom-field coupling ceases. The theory developed will provide useful physical insights for future experimental work and enhance significant knowledge on the nonclassicality of light in matter-wave interaction. The research results will particularly benefit quantum information technology.